Enduring national unity through enhancing happiness: hedonic and eudaimonic approaches - Sarif, Suhaimi Mhd; Ismail, Yusof (2011)
This paper examines the efforts to create enduring national unity in Malaysia by enhancing the citizens’ happiness from the welfare economics perspectives, particularly through the hedonic and eudaimonic approaches. While hedonic approach emphasizes on the tangible aspects of a person’s happiness, eudaimonic approach focuses on the realization of a person’s intangible aspect (i.e. self development potential). The paper argues that national unity in Malaysia can be endured through these approaches despite the diversity in faiths, races, and ideologies. The results from personal interview with 15 Malaysian executives of different faiths, races, and ideologies demonstrate that the executives do value tangible aspect (hedonic) to enhance their happiness, but hedonism alone is insufficient and not strong enough to endure national unity in the country. All economic resources should be managed to help integrate and reinforce tangible (hedonic) and intangible (eudaimonic) aspects of citizens’ well being. This study suggests that Malaysian employers (both private and public sectors) should review their remuneration scheme and incentives plan as an effort to enhance happiness and endure national unity at workplaces and in the society.